Comparison of the reactivity of isomeric 2H‐ and 3H‐naphthopyran mechanophores. Issue 21 (26th June 2021) - Osler, Skylar K.; McFadden, Molly E.; Robb, Maxwell J.
Abstract: Naphthopyrans are molecular switches that produce highly colored merocyanine dyes upon photochemical or mechanochemical activation in polymers. The mechanochromic behavior of these molecular force probes enables the straightforward visualization of stress and/or strain in materials. To date, research on the mechanochemistry of naphthopyran has largely focused on the 3 H ‐naphtho[2, 1‐ b ]pyran (3 H ) scaffold, whereas isomeric 2 H ‐naphtho[1, 2‐ b ]pyrans (2 H ) exhibit complementary properties as suggested from their photochemical reactivity. Here we directly compare the reactivity of two isomeric 2 H ‐ and 3 H ‐naphthopyran mechanophores in solution‐phase ultrasonication experiments and in crosslinked polydimethylsiloxane elastomers subjected to uniaxial tensile deformation. The prototypical 3 H ‐naphthopyran mechanophore produces a yellow merocyanine dye that reverts quickly, while the 2 H ‐naphthopyran mechanophore generates a red merocyanine dye that reverts significantly slower. The trends in absorption and reversion measured in solution are also reflected in solid polymeric materials activated in tension. Building on recent research into substituent effects, this study identifies naphthopyran isomerism as a simple lever for modulating the mechanochromic properties of the naphthopyran mechanophore used in the development of force‐responsive polymers. Abstract :